The Influence of the Application of the Game on Improving Motor Skills and Student Learning Motivation in Learning Physical Sport and Health Education (PSHE) - Zuhrotilanwar, Ahmad; S, Hartoto; Kartika, Dwi Cahyo (Journal of Physical Education Health and Sport, 2017)
This Research aimed to examine the effect of game implementation on improving motor skills and student learning motivation in PSHE learning in Seventh grade of 2nd semester student on SMPN 4 Lamongan.. This research used quantitative approach with research type of quasy experiment and using matching-only design. In this method the subject of research used two classes namely the seventh grade F, amounting to 28 students as an experimental group and the seventh grade I, amounting to 27 students as a control group. The data collection process was done by pretest and posttest stage using barrow motor ability test to measure motor ability and questionnaire to measure student’s learning motivation. The result of the research showed that there was a significant influence on the role of the game on the improvement of motor ability (7,56%) and there was a significant effect on the improvement of student’s learning motivation (8,28%) seen from t-test result. In addition there were differences in influence through the ANOVA test, as well as the role of the game was more influential than the control group in improving motor skills and student learning motivation. Based on the results of data analysis, it was concluded that learning by applying the game more effectively to improve motor skills and student learning motivation in learning PSHE but still need further development in subsequent research.